Organic Farming: A Solution to Agriculture Crisis or a “New” Trend to Healthy Eating? An Overview of French and British Farmers - Boulay, Annabelle (Journal for Geography, 2010)
In recent years, the market for organic farming has significantly increased in response to concerns over food quality and environmental matters. Organic food is quite attractive for consumers and is often associated to quality, healthy and natural products in opposition to the more processed and artificial conventional food. Yet, farmers are less enthusiastic about this concept. This paper, issued from a survey with dairy farmers in two dairy areas in France (January 2000) and the UK (July 2002), review farmers attitude towards organic farming. Only a minority of farmers were in favour of organic farming while the others had concerns about organic farming as its concept goes against their belief: a farmer must produce food for the nation